Open Access

Positive periodic solutions for neutral multi-delay logarithmic population model

Journal of Inequalities and Applications20122012:10

https://doi.org/10.1186/1029-242X-2012-10

Received: 7 March 2011

Accepted: 16 January 2012

Published: 16 January 2012

Abstract

Based on an abstract continuous theorem of k-set contractive operator and some analysis skill, a new result is obtained for the existence of positive periodic solutions to a neutral multi-delay logarithmic population model. Some sufficient conditions obtained in this article for the existence of positive periodic solutions to a neutral multi-delay logarithmic population model are easy to check. Furthermore, our main result also weakens the condition in the existing results. An example is used to illustrate the applicability of the main result.

MSC 2010: 34C25; 34D40.

Keywords

positive periodic solutionexistencek-set contractive operatorlogarithmic population model

1 Introduction

In recent years, there has been considerable interest in the existence of periodic solutions of functional differential equations (see, for example, [17]). It is well known that the environments of most natural populations change with time and that such changes induce variation in the growth characteristics of populations. Among many population models, the neutral logarithmic population model has recently attracted the attention of many mathematicians and biologists.

Let ω > 0 be a constant, C ω = {x : x C(R, R), x(t + ω) = x(t)}, with the norm defined by | x | 0 = max t [ 0 , ω ] x ( t ) , and C ω 1 = { x : x C 1 ( R , R ) , x ( t + ω ) = x ( t ) } , with the norm defined by ||x||0 = max{|x|0, |x'|0}, then C ω , C ω 1 are both Banach spaces. Let h ̄ = 1 ω 0 ω h ( t ) d t , h C ω .

Lu and Ge [8] studied the existence of positive periodic solutions for neutral logarithmic population model with multiple delays. Based on an abstract continuous theorem of k-set contractive operator, Luo and Luo [9] investigate the following periodic neutral multi-delay logarithmic population model:
d N d t = N ( t ) r ( t ) - j = 1 n a j ( t ) ln N ( t - σ j ( t ) ) - i = 1 m b i ( t ) d d t ln N ( t - τ i ( t ) )
(1)

where r(t), a j (t), b i (t), σ j (t), τ i (t) are all in C ω with r ̄ > 0 , σ j (t) > 0 and τ i (t) > 0, t [0, ω], j {1, 2, ..., n}, i {1, 2, ..., m}. Furthermore, b i (t) C1(R, R), σ j (t) C1(R, R), τ i (t) C2 (R, R) and σ j ( t ) < 1 , τ i ( t ) < 1 , j {1, 2, ..., n}, i {1, 2, ..., m}.

Since σ j ( t ) < 1 , t [ 0 , ω ] , t - σ j ( t ) has a unique inverse. Let μ j (t) be the inverse of t - σ j (t). Similarly, t - τ i (t) has a unique inverse, denoted by γ i (t).

For convenience, denote Γ ( t ) = j = 1 n a j ( μ j ( t ) ) 1 - σ j ( μ j ( t ) ) - i = 1 m b i ( γ i ( t ) ) 1 - τ i ( γ i ( t ) ) .

Luo and Luo [9] obtain the following sufficient condition on the existence of positive periodic solutions for neutral logarithmic population model with multiple delays.

Theorem A. Assume the following conditions hold:

( H 1') There exists a constant θ > 0 such that |Γ(t)| > θ, t [0, ω].

( H 2') j = 1 n | a j | 0 ω + i = 1 m | b i | 0 | 1 - τ i | 0 1 / 2 < 1 and i = 1 m | b i | 0 | 1 - τ i | 0 < 1 .

Then Equation (1) has at least an ω-positive periodic solution.

The purpose of this article is to further consider the existence of positive periodic solutions to a neutral multi-delay logarithmic population model (1). We will present some new sufficient conditions for the existence of positive periodic solutions to a neutral multi-delay logarithmic population model. In this article, we will replace the assumption (H 1'): |Γ(t)| > θ in Theorem A by different assumption Γ(t) > 0, t [0, ω], (or Γ(t) < 0, t [0, ω]). Obviously, it is more easy to check Γ(t) > 0, t [0, ω], than to find a constant θ > 0 such that |Γ(t)| > θ, t [0, ω]. At the same time, the assumption (H 2') in Theorem A will be greatly weakened. j = 1 n | a j | 0 ω + i = 1 m | b i | 0 | 1 - τ i | 0 1 / 2 < 1 in Theorem A is replaced by 1 2 j = 1 n | a j | 0 ω + i = 1 m | b i | 0 | 1 - τ i | 0 1 / 2 < 1 in this article.

2 Main lemmas

Under the transformation N(t) = ex(t), then Equation (1) can be rewritten in the following form:
x ( t ) = r ( t ) - j = 1 n a j ( t ) x ( t - σ j ( t ) ) - i = 1 m c i ( t ) x ( t - τ i ( t ) )
(2)

where c i ( t ) = b i ( t ) ( 1 - τ i ( t ) ) , i = 1 , 2 , , m .

It is easy to see that in this case the existence of positive periodic solution of Equation (1) is equivalent to the existence of periodic solution of Equation (2). In order to investigate the existence of periodic solution of Equation (2), we need some definitions and lemmas.

Definition 1. Let E be a Banach space, S E be a bounded subset, denote α E (S) = inf {δ > 0| there is a finite number of subsets S i S such that S = i S i and
d i a m S i δ }
then α E is called non-compactness measure of S or Kuratowski distance (see[1]), where diamS i denotes the diameter of set S i .

Definition 2. Let E1and E2be Banach spaces, D E1, A : DE2be a continuous and bounded operator. If there exists a constant k ≥ 0 satisfying α E 2 ( A ( S ) ) k α E 1 ( S ) for any bounded set S D, then A is called k-set contractive operator on D.

Definition 3. Let X, Y be normed vector spaces, L : DomL XY be a linear mapping. This mapping L will be called a Fredholm mapping of index 0 if dimKerL = codimImL <and ImL is closed in Y[3].

Assume that L : DomL XY is a Fredholm operator with index 0, from [3], we know that sup{δ > 0|δα X (B) ≤ α Y (L(B))} exists for any bounded set B DomL, so we can define
l ( L ) = sup { δ > 0 | δ α X ( B ) α Y ( L ( B ) ) for any bounded set B D o m L } .

Now let L : XY be a Fredholm operator with index 0, X and Y be Banach spaces, Ω X be an open and bounded set, and let N : Ω ̄ Y be a k-set contractive operator with k < l(L). By using the homotopy invariance of k-set contractive operator's topological degree D[(L, N), Ω], Petryshyn and Yu [10] proved the following result.

Lemma 1. [10]Assume that L : XY is a Fredholm operator with index 0, r Y is a fixed point, N : Ω ̄ Y is a k-set contractive operator with k < l(L), where Ω X is bounded, open, and symmetric about 0 Ω. Furthermore, we also assume that

(R 1) L x λ N x + λ r , λ ( 0 , 1 ) , x Ω D o m L ;

(R 2) [ Q N ( x ) + Q r , x ] [ Q N ( - x ) + Q r , x ] < 0 , x Ω K e r L .

where[·,·] is a bilinear form on Y × X, and Q is the projection of Y onto Coker, where Coker is the cokernel of the operator L. Then there exists a x Ω ̄ satisfying Lx = Nx + r.

In the rest of this article, we set Y = C ω , X = C ω 1
L x = d x d t
(3)
and
N x = - j = 1 n a j ( t ) x ( t - σ j ( t ) ) - i = 1 m c i ( t ) x ( t - τ i ( t ) ) ,
(4)
then Equation (2) is equivalent to the equation
L x = N x + r
(5)

where r = r(t). Clearly, Equation (2) has an ω-periodic solution if and only if Equation (5) has a solution x C ω 1 .

Lemma 2. [7]The differential operator L is a Fredholm operator with index 0, and satisfies l(L) ≥ 1.

Lemma 3. [9]If k = i = 1 n | c i | 0 , then N : Ω → C ω is a k-set contractive operator.

Lemma 4. [8]Suppose τ C ω 1 and τ'(t) < 1, t [0, ω]. Then the function t - τ (t) has a inverse μ(t) satisfying μ C(R, R) with μ(a + ω) = μ(a) + ω.

Lemma 5. [11]Let x(t) be continuous differentiable T-periodic function (T > 0). Then for any t* (-∞, +∞)
max t [ t * , t * + T ] | x ( t ) | | x ( t * ) | + 1 2 0 T | x ( s ) | d s .

3 Main results

Let μ j (t) be the inverse of t - σ j (t), γ j (t) be the inverse of t - τ i (t) and Γ ( t ) = j = 1 n a j ( μ j ( t ) ) 1 - σ j ( μ j ( t ) ) - i = 1 m b i ( γ i ( t ) ) 1 - τ i ( γ i ( t ) ) .

Theorem 1. Assume the following conditions hold:

(H 1) If Γ(t) > 0, t [0, ω] (or Γ(t) < 0, t [0, ω]);

(H 2) 1 2 j = 1 n a j 0 ω + i = 1 m b i 0 | 1 - τ i | 0 1 / 2 < 1 and i = 1 m b i 0 | 1 - τ i | 0 < 1 .

Then Equation (1) has at least an ω-positive periodic solution.

Proof. Suppose that x(t) is an arbitrary ω-periodic solution of the following operator equation
L x = λ N x + λ r
(6)
where L and N are defined by Equations (3) and (4), respectively. Then x(t) satisfies
x ( t ) = λ r ( t ) - j = 1 n a j ( t ) x ( t - σ j ( t ) ) - i = 1 m c i ( t ) x ( t - τ i ( t ) ) .
(7)
Integrating both sides of Equation (7) over [0, ω] gives
0 ω r ( t ) - j = 1 n a j ( t ) x ( t - σ j ( t ) ) + i = 1 m b i ( t ) x ( t - τ i ( t ) ) d t = 0
(8)
i.e.,
0 ω j = 1 n a j ( t ) x ( t - σ j ( t ) ) - i = 1 m b i ( t ) x ( t - τ i ( t ) ) d t = r ̄ ω .
(9)
Let t - σ j (t) = s, i.e., t = μ j (s). Lemma 4 implies that
a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) C ω , a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) x ( s ) C ω .

Lemma 4 implies μ j (0 + ω) = μ j (0) + ω, γ i (0 + ω) = γ i (0) + ω, j {1, ..., n}, i {1, ..., m}.

Noting that σ j (0) = σ j (ω), τ i (0) = τ i (ω), then
0 ω a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) d s = - σ j ( 0 ) ω - σ j ( ω ) a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) d s = 0 ω a j ( t ) d t = ω ā j , j = 1 , , n ,
(10)
0 ω b i ( γ i ( s ) ) 1 - τ i ( γ i ( s ) ) d s = - τ i ( 0 ) ω - τ i ( ω ) b i ( γ i ( s ) ) 1 - τ i ( γ i ( s ) ) d s = 0 ω b i ( t ) d t = 0 , i = 1 , , m .
(11)
Noting that Γ(t) > 0, we have
Γ ̄ = 1 ω 0 ω Γ ( t ) d t = 1 ω 0 ω j = 1 n a j ( μ j ( t ) ) 1 - σ j ( μ j ( t ) ) - i = 1 m b i ( γ i ( t ) ) 1 - τ i ( γ i ( t ) ) d t = j = 1 n ā j > 0 .
(12)
Furthermore
0 ω a j ( t ) x ( t - σ j ( t ) ) d t = - σ j ( 0 ) ω - σ j ( ω ) a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) x ( s ) d s = 0 ω a j ( μ j ( s ) ) 1 - σ j ( μ j ( s ) ) x ( s ) d s , j = 1 , , n .
(13)
Similarly
0 ω b i ( t ) x ( t - τ i ( t ) ) d t = - τ i ( 0 ) ω - τ i ( ω ) b i ( γ i ( s ) ) 1 - τ i ( γ i ( s ) ) x ( s ) d s = 0 ω b i ( γ i ( s ) ) 1 - τ i ( γ i ( s ) ) x ( s ) d s , i = 1 , , m .
(14)
Combining (13) and (14) with (9) yields
0 ω Γ ( t ) x ( t ) d t = r ̄ ω .
(15)
Since Γ(t) > 0, it follows from the extended integral mean value theorem that there exists η [0, ω] satisfying
x ( η ) 0 ω Γ ( t ) d t = r ̄ ω ,
(16)
i.e.,
x ( η ) = r ̄ Γ ̄ .
(17)
By Lemma 5, we obtain
| x ( t ) | | x ( η ) | + 1 2 0 ω | x ( t ) | d t .
So
| x | 0 | r ̄ Γ ̄ | + 1 2 0 ω x ( t ) d t .
(18)
Multiplying both sides of Equation (7) by x'(t) and integrating them over [0, ω], we have
0 ω | x ( t ) | 2 d t = 0 ω x ( t ) 2 d t = 0 ω x ( t ) 2 d t = λ 0 ω r ( t ) x ( t ) d t - 0 ω j = 1 n a j ( t ) x ( t - σ j ( t ) ) x ( t ) d t - 0 ω i = 1 m c i ( t ) x ( t - τ i ( t ) ) x ( t ) d t | r | 0 0 ω | x ( t ) | d t + j = 1 n | a j | 0 | x | 0 0 ω x ( t ) d t + i = 1 m 0 ω | c i ( t ) x ( t - τ i ( t ) ) x ( t ) | d t .
(19)
Cauchy-Schwarz inequality implies
0 ω | x ( t ) | 2 d t = λ | 0 ω r ( t ) x ( t ) d t 0 ω j = 1 n a j ( t ) x ( t σ j ( t ) ) x ( t ) d t 0 ω i = 1 m c i ( t ) x ( t τ i ( t ) ) x ( t ) d t | ( | r | 0 + j = 1 n | a j | 0 | x | 0 ) ( 0 ω | x ( t ) | 2 d t ) 1 / 2 ω 1 / 2 + i = 1 m ( 0 ω | c i ( t ) x ( t τ i ( t ) ) | 2 d t ) 1 / 2 ( 0 ω | x ( t ) | 2 d t ) 1 / 2 .
(20)
Meanwhile
( 0 ω | c i ( t ) x ( t τ i ( t ) ) | 2 d t ) 1 / 2 = ( 0 ω 1 1 τ i ( γ i ( t ) ) | c i ( γ i ( t ) ) x ( t ) | 2 d t ) 1 / 2 = ( 0 ω ( 1 τ i ( γ i ( t ) ) ) | b i ( γ i ( t ) ) x ( t ) | 2 d t ) 1 / 2 | 1 τ i | 0 1 / 2 | b i | 0 ( 0 ω | x ( t ) | 2 d t ) 1 / 2 .
(21)
Substituting Equations (18) and (21) into (20) gives
0 ω | x ( t ) | 2 d t ( | r | 0 + j = 1 n | a j | 0 | x | 0 ) ( 0 ω | x ( t ) | 2 d t ) 1 / 2 ω 1 / 2 + i = 1 m | 1 τ i | 0 1 / 2 | b i | 0 ( 0 ω | x ( t ) | 2 d t ) ( | r | 0 + j = 1 n | a j | 0 r ¯ Γ ¯ ) ( 0 ω | x ( t ) | 2 d t ) 1 / 2 ω 1 / 2 + [ 1 2 ω j = 1 n | a j | 0 + i = 1 m | 1 τ i | 0 1 / 2 | b i | 0 ] ( 0 ω | x ( t ) | 2 d t ) .
(22)
From the assumption 1 2 ω j = 1 n | a j | 0 + i = 1 m | 1 - τ i | 0 1 / 2 | b i | 0 < 1 , it follows from Equation (22) that there exists constant M > 0 such that
0 ω x ( t ) 2 d t 1 / 2 < M .
(23)
Then
x 0 r ̄ Γ ̄ + 1 2 0 ω x ( t ) d t r ̄ Γ ̄ + 1 2 M ω 1 / 2 : = M 1 .
(24)
Again from (7), we get
| x | 0 | r | 0 + j = 1 n | a j | 0 | x | 0 + i = 1 m | c i | 0 | x | 0 .
(25)
Condition i = 1 m | c i | 0 i = 1 m | b i | 0 | 1 - τ i | 0 < 1 implies that
| x | 0 | r | 0 + j = 1 n | a j | 0 M 1 1 - i = 1 m | c i | 0 : = M 2 .
(26)
Let M 3 > max { M 1 , M 2 , | r ̄ / j = 1 n ā j | } and Ω = { x | x C ω 1 , x < M 3 } . Then k = i = 1 m | c i | 0 < 1 l ( L ) . Equations (24) and (26) imply that all conditions of Lemma 1 except (R2) hold. Next, we prove that the condition (R2) of Lemma 1 is also satisfied. We define a bounded bilinear form [·,· ] on C ω × C ω 1 as follows:
[ y , x ] = 0 ω y ( t ) x ( t ) d t .
(27)
Define Q : YCokerL by
Q y = 1 ω 0 ω y ( t ) d t .
Obviously,
x | x k e r L Ω = { x | x = M 3 , x = - M 3 } .
Without loss of generality, we may assume that x = M3. Thus
[ Q N ( x ) + Q r , x ] [ Q N ( - x ) + Q r , x ] = M 3 2 0 ω r ( t ) d t - M 3 j = 1 n 0 ω a j ( t ) d t 0 ω r ( t ) d t + M 3 j = 1 n 0 ω a j ( t ) d t = ω 2 M 3 2 r ̄ - M 3 j = 1 n ā j r ̄ + M 3 j = 1 n ā j < 0 .
(28)

Therefore, by Lemma 1, Equation (1) has at least an ω-positive periodic solution.    □

Since | 1 - τ i | 0 < 1 , then | 1 - τ i | 0 < | 1 - τ i | 0 1 / 2 . So i = 1 m | b i | 0 | 1 - τ i | 0 < i = 1 m | b i | 0 | 1 - τ i | 0 1 / 2 . From Theorem 1, we have

Corollary 1. Assume that the following conditions hold

(H 1') I f Γ ( t ) > 0 , t [ 0 , ω ] ( o r Γ ( t ) < 0 , t [ 0 , ω ] ) .

(H 2') 1 2 j = 1 n | a j | 0 ω + i = 1 m | b i | 0 | 1 - τ i | 0 1 / 2 < 1 and | 1 - τ i | 0 < 1 , i = 1, ..., m.

Then Equation (1) has at least an ω-positive periodic solution.

4 Example

Example 1 is given to illustrate the effectiveness of our new sufficient conditions, also to demonstrate the difference between the proposed result in this paper and the result in [9].

Example 1. Consider the following equation:
d N d t = N ( t ) r ( t ) - 1 8 ( cos 2 t + 1 ) ln N ( t - π ) - 1 64 ( 3 - cos t ) d d t ln N ( t - π )
(29)

where r ( t ) = cos t - 1 32 ( cos 2 t + 1 ) sin t - 1 64 ( 3 - cos t ) cos t .

Let ω = 2π. Corresponding to Equation (1), we have n = m = 1, a 1 ( t ) = 1 8 ( cos 2 t + 1 ) , b 1 ( t ) = 1 64 ( 3 - cos t ) , σ1(t) = τ1(t) = π So r ̄ = 1 128 > 0 , σ 1 ( t ) = τ 1 ( t ) = 0 , μ 1 ( t ) = γ 1 ( t ) = π + t . Thus
Γ ( t ) = a 1 ( μ 1 ( t ) ) - b 1 ( γ 1 ( t ) ) = 1 8 ( cos 2 t + 1 ) + 1 64 sin t > 0 ,
1 2 | a 1 | 0 ω + | b 1 | 0 | 1 - τ i | 0 1 / 2 = 4 π + 1 16 < 1 .
The conditions in Theorem 1 in this article are satisfied. Hence Equation (29) has at least an 2π-positive periodic solution. However, the condition ( H 2 ) in Theorem A(Theorem 3.1 in[9]) is not satisfied. Since
| a 1 | 0 ω + | b 1 | 0 | 1 - τ i | 0 1 / 2 = 8 π + 1 16 > 1 ,

Theorem 3.1 in[9]can not be applied to this example. Let θ = 7 64 . Although the condition ( H 1 ) in Theorem A (Theorem 3.1 in[9]) is satisfied, it is more complex to check the condition |Γ(t)| > θ, t [0, ω] in Theorem A than to test Γ(t) > 0, t [0, ω]. This example illustrates the advantages of the proposed results in this paper over the existing ones.

Declarations

Acknowledgements

The authors are grateful to the referees for their valuable comments which have led to improvement of the presentation. This study was partly supported by the Zhong Nan Da Xue Qian Yan Yan Jiu Ji Hua under grant No. 2010QZZD015, Hunan Scientific Plan under grant No. 2011FJ6037, NSFC under grant No. 61070190 and NFSS under grant 10BJL020.

Authors’ Affiliations

(1)
School of Mathematical Science and Computing Technology, Central South University

References

  1. Deimling K: Nonlinear Functional Analysis. Springer, Berlin; 1985.View ArticleGoogle Scholar
  2. Gopalsamy K, He X, Wen L: On a periodic neutral logistic equation. Glasgow Math J 1991, 33: 281–286. 10.1017/S001708950000834XMATHMathSciNetView ArticleGoogle Scholar
  3. Gaines RE, Mawhin JL: Coincidence degree and nonlinear differential equation. In Lecture notes in Math. Volume 568. Springer, Berlin; 1997.Google Scholar
  4. Kirlinger G: Permanence in Lotka-Volterra equation, linked prey-predator system. Math Biosci 1986, 82: 165–191. 10.1016/0025-5564(86)90136-7MATHMathSciNetView ArticleGoogle Scholar
  5. Kuang Y: Delay Differential Equations with Applications in Population Dynamics. Academic Press, New York; 1993.Google Scholar
  6. Kuang Y, Feldstein A: Boundedness of a nonlinear nonautonomous neutral delay equation. J Math Anal Appl 1991, 156: 293–304. 10.1016/0022-247X(91)90398-JMATHMathSciNetView ArticleGoogle Scholar
  7. Liu ZD, Mao YP: Existence theorem for periodic solutions of higher order nonlinear differential equations. J Math Anal Appl 1997, 216: 481–490. 10.1006/jmaa.1997.5669MATHMathSciNetView ArticleGoogle Scholar
  8. Lu SP, Ge WG: Existence of positive periodic solutions for neutral logarithmic population model with multiple delays. J Comput Appl Math 2004, 166(2):371–383. 10.1016/j.cam.2003.08.033MATHMathSciNetView ArticleGoogle Scholar
  9. Luo Y, Luo ZG: Existence of positive periodic solutions for neutral multi-delay logarithmic population model. Appl Math Comput 2010, 216: 1310–1315. 10.1016/j.amc.2010.02.024MATHMathSciNetView ArticleGoogle Scholar
  10. Petryshyn WV, Yu ZS: Existence theorems for higher order nonlinear periodic boundary value problems. Nonlinear Anal 1982, 9: 943–969.MathSciNetView ArticleGoogle Scholar
  11. Tang ML, Liu XG, Liu XB: New results on periodic solution for a kind of Rayleigh equation. Appl Math 2009, 54: 79–85. 10.1007/s10492-009-0006-8MATHMathSciNetView ArticleGoogle Scholar

Copyright

© Tang and Tang; licensee Springer. 2012

This article is published under license to BioMed Central Ltd. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.